Career Adaptability in College Students: The Role of Proactive Personality and Perceived Social Support - Robbani, Aurel Bernika; Mulyana, Olievia Prabandini (Universitas Pamulang, 2026)
The dynamic evolution of modern career orientations necessitates that individuals assume responsibility for defining their own career pathways. Moreover, it is essential for students to recognize these changes, as their awareness significantly impacts career adaptability development, a critical strategy for effectively navigating the transition from education to the workforce. This study aims to examine the impact of proactive personality and perceived social support on career adaptability among students from various educational backgrounds. The research employs a quantitative correlational survey design, involving 127 students with internships, part-time, or full-time work experience. The analysis conducted using the Pearson correlation test revealed a significant positive correlation between proactive personality and social support in career adaptability. The findings indicate that proactive personality contributed 40% to career adaptability, while social support contributed 22%. These results indicate that career adaptability is fundamentally a self-regulated process driven by individual agency, while social support functions primarily as a facilitator rather than a primary driver. Consequently, higher education institutions are advised to prioritize career interventions that cultivate students' internal psychological resources to prepare adaptable graduates.